Penerapan Manajemen Bandwith Menggunakan Hierarchical Token Bucket Di PT. Bukit Energi Servis Terpadu - Alvin Riady; Aan Restu Mukthi (Jurnal Pengembangan Sistem Informasi dan Informatika, 2021)
Bukit Energi Servis Terpadu (BEST) is a company engaged in Operation & Maintenance (O&M) services which are members of the PT group. Bukit Asam Tbk. PT. Bukit Energi Servis Terpadu (BEST) already has a computer network in the form of adequate wired and wireless networks and has been connected to the internet. The bandwidth used for the scope of the office uses a bandwidth of 30 Mbps, but the problem of internet speed is not maximized where there is download activity and video streaming which causes the internet bandwidth in the office to be slow, thus affecting the activities of employees who are accessing the internet in the office either through wired networks and wireless internet hotspots. The results of the measurement of packet loss parameters (%) after Bandwidth Management with HTB is better, namely 0.12 % while before Bandwidth Management with HTB is carried out with a value of 0.52 %. The results of measuring the throughput parameters before using Bandwidth Management with HTB where the use of throughput after using Management Bandwidth with HTB obtained results of 624.9 kbps while the throughput before Bandwidth Management was carried out was 624.4 kbps. By limiting bandwidth using the Hierarchical Token Bucket (HTB) facility, bandwidth can be divided into certain sections or prioritized for those who need higher internet speeds, while those that do not require an internet connection are provided with a small speed.